Epicapsular Stars : A Rare Entity (Global Journal of Medical Research, 2022)
An 18-year-old female presented to the ophthalmology clinic for allergic conjunctivitis with a 20/20 best-corrected visual acuity. Slit-lamp examination of her left eye revealed, fortuitously, multiple tiny, stellate-shaped, pigment deposits on the anterior lens capsule suggestive of Epicapsular stars. These pigmentations were clustered in an exceptional shape reminiscent of the letters "J" and "Y" Epicapsular stars result from incomplete apoptosis of the anterior portion of #x2018;#x2019;tunica vasculosa lentis#x2019;#x2019;. They could affect one or both eyes, be isolated or clustered, and are usually asymptomatic like in our case. Consequently, our patient didn#x2019;t need any treatment but has still followed up regularly.